Konsep Inovasi Kewirausahaan di Era Disruptif - Heny May Widiyawati; Cecep Castrawijaya (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines how entrepreneurs innovate in an era of disruption when technology is rapidly changing the business landscape. The study identified three key success factors: the ability to adapt quickly to change, a customer-focused approach, and strategic partnerships. Entrepreneurs who view disruption as an opportunity rather than a threat have a success rate three times higher than others. The findings suggest that modern entrepreneurial innovation extends beyond product development to business model transformation, digital technology adoption, and stakeholder relationship building. The study concludes that entrepreneurs who succeed in a disruptive environment must be able to embrace change, maintain a customer focus, and develop flexible strategies to navigate current market volatility.